Country of the cursed and the driven : slavery and the Texas borderlands - Barba, Paul (Borderlands and transcultural studies., 2021)
A sweeping, comparative analysis of the slaving regimes of Hispanic, Comanche, and Anglo American communities in the Texas borderlands during the eighteenth and nineteenth centuries.